Tradisi Peciho Mata Mual Sebagai Upaya Meningkatkan Keharmonisan Keluarga Luas Bagi Masyarakat Pakpak Klasen Di Kecamatan Parlilitan Kabupaten Humbang Hasundutan - Febriyani Nurcahaya Tinambunan; Jupalman Welly Simbolon; Masniar Hermawati Sitorus; Elvri Teresia Simbolon; Roida Lumbantobing (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research uses a qualitative approach and the type of research is descriptive, namely to understand the phenomenon that describes and describes an event of the peciho mata mual tradition in an effort to improve harmony in the extended family carried out in the Pakpak Klasen community in Sionom Hudon Toruan village in Parlilitan sub-district, Humbang Hasundutan district, using the collection method. data includes observation, interviews, documentation. The focus of this problem is: 1. The existence of the Peciho Mata Mual tradition in an effort to increase extended family harmony in the Pakpak Klasen community in Parlilitan sub-district, Humbang Hasundutan district. hasundutan. 2. The Peciho Mata Mual tradition is an effort to extended family harmony for the Pakpak Klasen community in Parlilitan sub-district, Humbang Hasundutan district. 3. Peciho Mata Mual has become an aspect of modern life for the Pakpak Klasen community in Parlilitan sub-district, Humbang Hasundutan district. The results of this research conclude: The existence of the Peciho Mata Mual tradition that has existed from the past and exists to this day, where the Peciho Mata Mual tradition in Sionom Hudon Toruan village, Parlilitan sub-district is carried out to increase harmony in the wider family in accordance with the stages in the Peciho Mata Mual tradition. This tradition is carried out because it is obligatory according to custom and there are problems in the family if you have not carried out this tradition, namely the connection between the bones and the berenya is almost tenuous and less harmonious, and Peciho Mata Mual has become an aspect of modern life for the Pakpak Klasen community in Sionom Hudon Toruan Village, Parlilitan District, Regency. Humbang hasundutan, because of its unique cultural heritage and traditions which are an opportunity to strengthen ties of brotherhood among families and society as a whole.